2014
DOI: 10.1177/1464884913520198
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering ‘virtuous circle’ and ‘media malaise’ theories of the media: An 11-nation study

Abstract: This study, based on a content analysis of television news and survey in eleven nations, explores the split between those who see the media as politically alienating and others who see the media as encouraging greater political involvement. Here, we suggest that both positions are partly right. On the one hand, television news, and in particular public service television news, can be very effective in imparting information about public affairs and promoting a culture of democracy in which news exposure, public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 49 publications
4
64
1
5
Order By: Relevance
“…We found a consistent pattern in which publicly owned channels reported more public affairs news than private channels, and after controlling for other influences, A third study, this time based on eleven countries around the globe, again found that public service broadcasting (PSB) fostered higher levels of public affairs knowledge (SOROKA, 2013). Consumption of PSB news, in particular, seemingly gave rise to a mutually reinforcing dynamic of enhanced political knowledge, political interest and sense of political efficacy (CURRAN et al, 2014).…”
Section: Entertaining Democracy In the Era Of Neo-liberalismsupporting
confidence: 56%
See 1 more Smart Citation
“…We found a consistent pattern in which publicly owned channels reported more public affairs news than private channels, and after controlling for other influences, A third study, this time based on eleven countries around the globe, again found that public service broadcasting (PSB) fostered higher levels of public affairs knowledge (SOROKA, 2013). Consumption of PSB news, in particular, seemingly gave rise to a mutually reinforcing dynamic of enhanced political knowledge, political interest and sense of political efficacy (CURRAN et al, 2014).…”
Section: Entertaining Democracy In the Era Of Neo-liberalismsupporting
confidence: 56%
“…These are contributing to a growing sense of alienation from the political process. Thus, in an eleven nation study I and colleagues carried out in 2010, 35% of respondents agreed or agreed strongly with the statement that "no matter who people vote for, it won't make any difference to what happens" (CURRAN et al, 2014).…”
Section: Entertaining Democracy In the Era Of Neo-liberalismmentioning
confidence: 93%
“…In taking account of national differences in the supply of, and demand for, news, the research sought to establish the influence of national political and media systems on citizen knowledge of public affairs. Thus, by extension, the project analysed the degree to which the organization of the media, and the societies in which they are embedded, affect the quality of political citizenship in a diverse range of national contexts, thereby allowing comparative conclusions to be drawn (see Curran et al 2013a).…”
Section: Sources In the Newsmentioning
confidence: 99%
“…In addition, two newspapers*a prestigious quality newspaper and, where applicable, a large-circulation popular newspaper (although in several countries it was more appropriate to study two quality newspapers)*were analysed, as well as the leading news website in each country. Curran et al (2013a) provide greater methodological detail on the research design across the whole project.…”
Section: Sources In the Newsmentioning
confidence: 99%
“…The democratic deficit characterizes many western democracies (Dalton 2004;Norris 2011;van Deth et al 2007) and is particularly relevant to Italy and the United Kingdom, the two countries this article focuses on, where many citizens are dissatisfied with mainstream political parties and institutions (Curran et al 2014), and participation in formal party politics has decreased sharply in the last two decades (Segatti 2006;Whiteley 2012). In this context, the Internet has been identified as a sort of 'magic elixir' able to increase citizens' participation and, consequently, to legitimize democratic governments (Stromer-Galley 2003).…”
Section: Introduction: Democratic Deficit and Political Participationmentioning
confidence: 99%